Comparative Study Assessing Postoperative Renal Loss Using Two Different Partial Nephrectomy Techniques: Off-Clamp versus Standard On-Clamp Surgery - Aquil, Shahid (Curr Urol, 2020)
OBJECTIVES: To evaluate a case-matched study comparing postoperative renal function using two surgical techniques: an off-clamp partial nephrectomy (PN) with the aid of the Altrus® device and a standard on-clamp laparoscopic PN. MATERIAL AND METHODS: A total of 36 patients underwent PN. Eighteen had the off-clamp technique and 18 had the standard laparoscopic on-clamp PN. Demographic, clinical, radiological, and perioperative data were collected for analysis. An emphasis on renal function was made by analyzing both the perioperative and follow-up with estimated glomerular filtration rate and MAG3. RESULTS: The median values did not signifcantly differ for age, Charlson Comorbidity Index, and hospital stay in the off-clamp versus on-clamp PN [62.5 (interquartile range, IQR 11) vs. 60 (IQR 16) years, 4 (IQR 2) vs. 5 (IQR 2) and 5 (IQR 1) vs. 4 (IQR 2) days], respectively. The median diameter of the tumors was 33 (IQR 23) versus 41 (IQR 28) mm (p = 0.63), with median R.E.N.A.L. nephrometry scores of 7 (IQR 2) versus 7 (IQR 2) (p = 0.33). There was greater blood loss in the Altrus® (375 vs. 200 ml, p = 0.037). The clamp time in the on-clamp group was 30 (IQR 6) minutes (range 22-68 minutes) compared to 0 minutes in the off-clamp group. There was no difference in hemoglobin or creatinine levels between the groups. However, the on-clamp group had a significant loss in ipsilateral renal function on the MAG3 scan (49 vs. 42%, p = 0.0001), whereas the off-clamp group had no difference (48 vs. 46%, p = 0.72). CONCLUSIONS: The off-clamp method for PN is a feasible and safe option with better preservation of ipsilateral renal function when compared with on-clamp PN in the treatment of small renal masses.